Jenis Tanaman Obat Yang Dikonsumsi Yang Ditanam Di Pekarangan Pada Beberapa Lokasi Wilayah Indonesia Periode Tahun 2012 Sampai Dengan Tahun 2022 - Putri, Audrelya Jeannette Thomas; Thamrin, Rahmawati; Dwirosalia NS, Desi (Fakultas Kedokteran Universitas Bosowa, 2023)
Family medicinal plants are several types of selected medicinal plants that are planted in the yard of the house or the environment around the house. The selected medicinal plants are usually medicinal plants that can be used for first aid or as light medicines. The purpose of this study was to determine the types of medicinal plants consumed which were grown in the yards of residents in several locations in Indonesia for the period 2012 to 2022. The research method used in this study was a systematic review method with a descriptive observational approach by describing the research results obtained of eleven scientific research articles. The results of the research from eleven research journals obtained 37 types of garden medicinal plants recorded in research journals including types of herbal medicinal plants, types of medicinal herbs for kitchen spices, types of medicinal vegetable plants and types of fruit medicinal plants.